Power conversion efficiency (PCE) performance of back-illuminated DSSCs with different Pt catalyst contents at the optimized TiO2 thickness - Shamsudin N.H.; Shafie S.; Ab Kadir M.Z.A.; Ahmad F.; Sadrolhosseini A.R.; Sulaiman Y.; Chachuli S.A.M. (Elsevier GmbH, 2023)
Anodes; Catalyst activity; Conversion efficiency; Dye-sensitized solar cells; Efficiency; Thick films; Tin oxides; Titanium dioxide; Back-illuminated; Catalytic capability; Fluorine tin oxides; Front illuminated; Power conversion efficiencies; TiO2; Titanium dioxides (TiO2); Titanium foils; Platinum